INOVASI PELAYANAN SIM BOOKING DI SATLANTAS POLRES KUDUS - Aron Sebastian (Dialogue : Jurnal Ilmu Administrasi Publik, 2019)
In order to adapt in changing environment, innovation is an important component in public organization. Innovation in public organization runs in two stages, the initiation stage and the implementation stage. The study examines supporting factors and barriers of innovation at the Driving Licence service agency. The paper analyzes the initiation stage and the implementation stage. In the initiation stage, the article shows the agency’s decision to impement "SIM Booking Innovation" as policy to respond to the demands of the community and organization. At implementation stage, the agency implement a more technical intervention by building infrastructure such as allocating special booth and staff, For driving license extension procedure, the agency adopted the existing model. In conclusion, the article argues that the supporting factors in organization innovation consists of broad-minded and open-minded leaders, availability of facilities, and organizational support in the implementation of innovation. On the other hand, the barrier factors of innovation are the lack of special budget to support innovation program, risk aversion of subordinates and over-reliance on high-performers.